A Multiple Unit Abuse-deterrent Dosage Form Based on Sodium Alginate - Papadakos M.; Špaglová M.; Čuchorová M.; Hanko M. (Sciendo, 2023)
There are several approaches for the formulation of abuse-deterrent, tamper-resistant, or alcohol-resistant dosage forms. This work is specifically focused on the formulation of microforms and multiple unit dosage forms with the mentioned resistant features. We prepared microcapsules based on sodium alginate by Ca2+-induced gelation, containing caffeine as a model drug. The prepared microcapsules were dried either by hot air or freeze-dried and the resistance in an alcoholic environment and the resistance against mechanical stress were observed. Subsequently, swelling studies were conducted to predict the behavior of prepared microcapsules during dissolution testing. Differences in the behavior of microcapsules during dissolution testing were strongly related to the different abilities of Ca2+-alginate microcapsules to swell in an acidic and alkaline environment. Alginate microcapsules exhibited gastro-resistant properties due to excellent swelling in an alkaline environment and poor swelling in a gastric environment. The addition of ethanol did not influence the swelling behavior of alginate microcapsules in the gastric fluid; rather, it showed the opposite effect, where swelling was slightly suppressed. Therefore, we conclude that alginate microcapsules are alcohol resistant. Also, they showed high mechanical strength, and therefore, grinding the microcapsules into a powder was impossible.